SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA PEGAWAI PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN PUCUK MENGGUNAKAN METODE AHP BERBASIS WEB - Ubaidilla Maghfur; M Hasan Wahyudi (Universitas Islam Lamongan, 2018)
Decision Support System is Information management aids system that deals with the calculation and assessment of employees in sub-district service, many ways to assess employee performance but this system that I created, as in advance company this system is often in use. In this research using AHP method. Making this performance appraisal decision support system using a web system. The system was created can provide an appraisal to assess the work of employees in PATENT